When is universal SEL effective under authentic conditions? Using LPA to examine program implementation in elementary classrooms - Zhao, Hui; Lei, Pui-Wa; Hart, Susan Crandall; DiPerna, James Clyde; Li, Xinyue (Frontiers in Education, 2023)
As universal social-emotional learning (SEL) programs have become more common in K-12 schools, implementation practices have been found to affect program quality. However, research examining how multiple facets of program implementation interrelate and impact student outcomes, especially under routine conditions in schools, is still limited. As such, we used latent profile analysis (LPA) to examine implementation of a brief universal SEL program (Social Skills Improvement System SEL Classwide Intervention Program; Elliott & Gresham, 2017) in primary classrooms. Three latent profiles of implementation were identified based on dosage, adherence, quality of delivery, student engagement and teachers’ impression of lessons. Although results suggested that classrooms with moderate- and high-level implementation practices generally showed higher gains in student outcomes than those with low-level implementation, these differences did not reach statistical significance except for academic motivation. Implications for school-based universal SEL program planning, implementation, and evaluation are discussed.